The Role of Political Thought in the Japanese Renaissance: A Study in the Ideas of Shiga Shigitaka (1863-1927) - Rabea, Hade (Dirasat: Human and Social Sciences, 2023)
Objectives: The study aims to shed light on Japanese political thought by getting acquainted with the views of one of the most important Japanese thinkers who had a great role in presenting the visions and ideas that contributed to enhancing the factors of development and the causes of the Japanese rise in the late nineteenth century and early twentieth century, namely, the Japanese thinker Shiga Shigitaka (1863-1927), who was considered one of the most important intellectuals of the Meiji and Taisho era. The study relied on the descriptive analysis method according to the previous method of the study. Results: The importance of Shiga Shigitaka’s ideas came from the accuracy of his analysis and his knowledge of the problems that have come to face Japanese society with the beginnings of its modernization experience while providing appropriate solutions to these problems. Conclusions: The thinker Shiga Shigitaka made great contributions to the modern Japanese renaissance, at the moment when Japan was exposed to external challenges that threatened its existence and survival as a nation after concluding unequal agreements with external powers that began knocking on the doors of Japan at this time, which later led to a revolution Meiji, and its initiation in the process of modernizing the country.